Deaf Education And Teachers Training in Zambia - Chibesa R. Simbule (Bandar Lampung University (UBL), 2014)
This article provides professional perspective of a teacher-training model which relies heavily on an intensive, culturally immersive field experience for the teacher of the Deaf and hard of hearing. Survey results were based upon 21 participants concerning their perceptions during their three-year internship experience in Zambia. Formal and informal periodic evaluations of participants reinforced the author's perspectives that an intensive yearlong residential experience is critical for developing the linguistic, fluency, and cultural awareness that are not only vital but also indispensable for teachers of D/hh (Deaf and Hard of Hearing) students. (This study does not intend to endorse any philosophy of the education of the Deaf. This study adopts an eclectic approach to teaching different philosophies for D/hh students.)